Efficacy of RB gene in transgenic potato Katahdin SP904 and SP951 to West Java isolates of Phytophthora infestans - Ambarwati, A. Dinar; Sumaraw, S. M.; Purwito, Agus; Herman, M.; Suryaningsih, E.; Aswidinnoor, Hajrial (Jurnal AgroBiogen, 2011)
Potato late blight, caused by Phytophthora infestans is one of the most devastating plant disease. Potato yield losses due to this disease ranged from 47-100%. A major late blight resistance gene, called RB, previously was identified in the wild potato species Solanum bulbocastanum. RB gene has been integrated into cultivated potato Katahdin using Agrobacterium-mediated transfor-mation, and showed durable and broad spectrum resistance either in laboratory assay or in confined field trial. Evaluation of transgenic Katahdin SP904 and SP951 was conducted to verify whether the RB gene with broad spectrum to all known races of P. infestans in the United States and in Toluca, Mexico was also effective against P. infestans isolates in Indonesia. Efficacy of RB gene was evaluated for foliar and tuber resistance to West Java isolates. Transgenic Katahdin were more resistant in foliar than non transgenic plants, at 14 days after inoculation. Diseases intensity of transgenic Katahdin SP904 and SP951 were 19.8-43.8%, whereas non transgenic Katahdin, Granola, and Atlantic were 46.9-100%. In contrast to the foliar resistance phenotype, RB-containing tubers in transgenic Katahdin did not exhibit increased resistance to Lembang, Pangalengan and Galunggung isolates. Tubers of transgenic Katahdin SP904, SP951, and non transgenic Katahdin showed lesion volume of 0.93, 0.91, and 0.91 cm3, respectively. RB gene in transgenic Katahdin showed efficacy against late blight P. infestans in foliar, but did not showed efficacy in tuber. Transgenic Katahdin RB thus providing a potential source of resistance for breeding programs.